Structural integrity of additive manufactured parts - Shamsaei, Nima (ASTM International, 2020)
"This compilation of Selected Technical Papers, STP1620, Structural Integrity of Additive Manufactured Parts, contains peer-reviewed papers that were presented at a symposium held November 6-8, 2018, in Washington, DC, USA. The symposium was sponsored by ASTM International Committee F42 on Additive Manufacturing Technologies, with co-sponsorship from Committees E08 on Fatigue and Fracture and E07 on Nondestructive Testing"-- Provided by publisher.
Keywords: Three-dimensional printing -- Congresses.; Machine parts -- Testing -- Congresses.; Machine parts -- Design and construction -- Congresses.; elektronické knihy; electronic books